Ichthyofaunal diversity and fishery status of Sutrapada Coast, Gujarat, India - Santosh Kumar Singh; Kangkan Jyoti Sarma; Dhaval M. Bhatt; Pradeep C. Mankodi (Journal of Fisheries, 2021)
Gujarat being a state having largest coastline and highest continental shelf in India represents diverse coastal habitats. Gujarat has vast potential of marine bioresources and offer considerable scope for marine fisheries. The ichthyofaunal diversity of Sutrapada, Gir Somnath district, Gujarat was investigated for a period of three years from June 2015 to June 2018 through the analysis of fish catch data of trawl fisheries and achieves of Fisheries Department, Central Institute of Fisheries Technology - Central Marine Fisheries Research Institute (CIFT-CMFRI), Marine Products Export Development Authority (MPEDA) and Commissioner Fisheries Office, Veraval. During this study period, 114 fish species belonging to 55 families and 93 genera were identified. The paper emphasizes the importance of further research on respective families for understanding of its distribution, ecology and conservation status.